PARLEMEN DAN DEMOKRATISASI: PERAN DEWAN PERWAKILAN RAKYAT DALAM TRANSISI DEMOKRASI DI INDONESIA - Yuwanto Yuwanto (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
The end of the authoritarian Suharto’s Orde Baru marked a crucial turning point not only for the country, but for the parliament as well. Indonesia’s parliament has been both subject as well as object of the transition process. A subject because it was actively involved in the regime change and the establishment of a more democratic order, and an object because the composition, status and fuctions of this institution were part of the deals in the debates on constitutional and legal change. Therefore, this article argued, against the theoritical mainstream, that the institution of parliament is important during the period of democratic transition.